Student’s Comprehension About Philosiphy of Maternity Care “Women Centered Care” Based on the Report of Continuity of Care (COC) - Rr Sri Nuriaty Masdiputri; Yanti Yanti; Asri Hidayat (Universitas Andalas, 2019)
Background: Mortality in Indonesia has significantly increased. Students’ comprehension about maternity care “woman centered care” philosophy is an important thing in high quality maternity care, it is one solution to decrease the number of mortality rate. Continuity of care maternal clinic model of learning (PKK-CoC) is giving for student to learn the philosophy.Objectives: reveals level and form of students’ comprehension about maternity care “woman centered care” philosophy.Method: Mixed method with sequential explanatory strategy. The quatitative are use analitic descriptive design, while the quantitative use case study design. Population and sample is 55 students of Estu Utomo Boyolali institute health and science who have taken PKK-CoC. Sampling use criterion and intensity.Result: qualitatively, students overall comprehension is good. Quantitatively, students comprehension on personalized care, holistic care, collaborative care, and evidence based care is also good. Partnership care is the only aspect considered in effective.Conclusion: continuity of care shows that client and family are in good heatlth, zero mortality rate, client fells safe and comfortable, and client has correct and fast care. It is also found that students’ confidence, skills, and comprehension about maternity care “woman centered care” philosophy are increased. It is suggested including the PKK-CoC model into curriculum of midwifery education